Multigenerational autosomal dominant inheritance of 5p chromosomal deletions. Issue 3 (24th November 2015) - Zhang, Bin; Willing, Marcia; Grange, Dorothy K.; Shinawi, Marwan; Manwaring, Linda; Vineyard, Marisa; Kulkarni, Shashikant; Cottrell, Catherine E.
Abstract : Deletion of the short arm of chromosome 5 (5p‐) is associated with phenotypic features including a cat‐like cry in infancy, dysmorphic facial features, microcephaly, and intellectual disability, and when encompassing a minimal critical region, may be defined as Cri‐du‐Chat syndrome (CdCS). Most 5p deletions are de novo in origin, and familial cases are often associated with translocation and inversion. Herein, we report three multigenerational families carrying 5p terminal deletions of different size transmitted in an autosomal dominant manner causing variable clinical findings. Terminal 5p deletions and the mode of inheritance were clinically characterized and molecularly analyzed by a combination of microarray and fluorescence in situ hybridization analyses. Shared phenotypic features documented in this cohort included neuropsychiatric findings, poor growth, and dysmorphic facial features. This study supports newly recognized effects of aberrant SEMA5A and CTNND2 dosage on severity of autistic and cognitive phenotypes. Comparative analysis of the breakpoints narrows the critical region for the cat‐like cry down to an interval less than 1 Mb encompassing a candidate gene ICE1, which regulates small nuclear RNA transcription. This study also indicates that familial terminal 5p deletion is a rare presentation displaying intra‐ and inter‐familial phenotypic variability, the latter of which may be attributed to size and gene content of the deletion. The observed intra‐familial phenotypic heterogeneity suggests that additional modifying elements including genetic and environmental factors may have an impact on the clinical manifestations observed in 5p deletion carriers, and in time, further high resolution studies of 5p deletion breakpoints will continue to aid in defining genotype–phenotype correlations. © 2015 Wiley Periodicals, Inc.